Ioannis Calvini Scripta Didactica et Polemica. Vol. 4, Epistolae Duae (1537), Deux Discours (Oct. 1536). - Jenkins, Gary W. (Sixteenth Century Journal)
The article reviews the book "Ioannis Calvini Scripta Didactica et Polemica. Vol. 4, Epistolae Duae (1537), Deux Discours (Oct. 1536)," edited by Erik Alexander de Boer and Frans Pieter van Stam.